ANALISIS PERANCANGAN STRUKTUR BANGUNAN ATAS JEMBATAN AMPERA DI SUNGAI DIGOEL PAPUA - Setiati, N. Retno (CANTILEVER, 2019)
Digoel river which separates between the western and eastern parts of Boven Digoel is a type of meander river (winding).Digoel river flow always changes in each period, so that the type of river Digoel influenced the method of designing and implementing the construction of a bridge that connecting Tanah Merah with Kampung Ampera significantly.  The aim of this study wasto analyze the results of the feasibility study relating to the design of upper structures of Ampera bridge in Boven Digoel, Papua.  The research method was carried out by conducting the laboratory and field experiments to obtain parameters in designing a bridge.  The laboratory experiments which had beenconductedwereaggregate materials (sand and gravels) and river water content tests.  The fieldexperiments were topography, bathymetry, geoelectric, and soil tests.  The structural analysis were conducted using a computer program (MIDAS), then based on the obtained data from the analysis results and evaluation, the type of bridge and planningcould be determined.  The Ampera Bridge that connects Tanah Merah with the village of Ampera was designed using a type of curved bridge ona main span of 200 meters.  The approach bridge was built by a span of 40 meters and 60 meters of steel frames.  The total length of the planned bridge is 600 meters.